The Effect of Risk Factors on Cardiovascular Diseases in Thi-Qar Governorate: Pengaruh Faktor Risiko terhadap Penyakit Kardiovaskular di Kegubernuran Thi-Qar - Kazim , Hajar Abdelkarim; Salman , Ali Naeem (Universitas Muhammadiyah Sidoarjo, 2025)
The purpose of this research was to identify the role of risk variables in the onset and progression of cardiovascular illnesses. There was a significant difference (P ≤0.05) between the two groups, with the sick group having a 36% higher smoking rate than the control group's 12% rate. A comparison between the patient group and the control group revealed that total cholesterol, triglycerides, and low-density lipoprotein (LDL) concentrations were all higher in the former, while HDL concentrations were lower. With 64% of patients experiencing hypertension and 36% not experiencing it, the percentages of patients with hypertension and those without it are much greater. There was a greater prevalence of type 2 diabetes among patients (60% vs. 40%), as well as other metabolic disorders. Among the other findings, 38% of patients were considered to be at a normal weight, 40% were considered to be overweight, and 24% were classified as having first-class obesity Highlights: Higher smoking rate, cholesterol, LDL, and lower HDL in patients. Increased hypertension (64%) and type 2 diabetes (60%) prevalence. 40% overweight, 24% obese, 38% normal weight among patients. Keywords: Heart and Vascular diseases, Rask Factors.